Assessing the Potential Benefit of Trade Facilitation: A Global Perspective - Wilson, John S.; Mann, Catherine L.; Otsuki, Tsunehiro (World Bank, Washington, D.C., 2013)
The relationships between trade facilitation, trade flows, and capacity building are complex and challenging to assess, both empirically and in implementation. The authors measure and estimate the relationship between trade facilitation and trade flows across 75 countries in global trade, considering four important categories: port efficiency, customs environment, regulatory environment, and service sector infrastructure. A gravity model is employed that accounts for bilateral trade flows in manufactured goods in 2000-01 between the 75 countries, using traditional factors such as GDP, distance, language, and trade areas, and is augmented by the trade facilitation measures in the four categories for each country. The results suggest that both imports and exports for a country and for the world will increase with improvements in these trade facilitation measures. Potential gains from trade facilitation reforms are predicted by using the estimated parameters. The gains from trade facilitation are presented by comparing the gains across geographical regions and trade facilitation categories, and by domestic and partner improvements. The total gain in trade flow in manufacturing goods from trade facilitation improvements in all the four areas is estimated to be $377 billion. All regions gain in imports and exports. Most regions gain more in terms of exports than imports, in large part through increasing exports to the OECD market. The most important ingredient in getting these gains, particularly to the OECD market, is the country's own trade facilitation efforts. The detailed presentation of the results of the analysis may help inform policy decisions and capacity building choices.